2010
DOI: 10.1111/j.1600-0463.2010.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Toll‐like receptor (TLR) 2, TLR4, and regulatory T cells in patients with chronic hepatitis C

Abstract: The mechanism of hepatitis C virus (HCV) involvement in innate immune responses and immune modulation has not been well characterized. In the present work, we studied Toll-like receptor (TLR) 2 and TLR4, which were recently recognized as the important components of innate immunity, as well as CD4+ CD25+ CD127low/- regulatory T cells (Tregs), which actively suppress pathological and physiological immune response during HCV infection. The study involved 31 chronic hepatitis C patients and 20 healthy controls. TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 29 publications
1
42
1
Order By: Relevance
“…NSC 78206 (cluster 3), also known as cyclobenzaprine, is a muscle relaxant used to relieve skeletal muscle spasms in acute musculoskeletal conditions (64). NSC 78206 is a tricyclic analog compound, which may be relevant because tricyclics and their active metabolites have been shown to have various biological functions, such as modulation of TLR4 and TLR2 signaling (36), whose expression and signaling are known to affect HCV (33,50,76) and inhibition of the drug-metabolizing enzyme aldehyde oxidase (55). In this study, we found that NSC 78206 inhibited JFHpp entry ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSC 78206 (cluster 3), also known as cyclobenzaprine, is a muscle relaxant used to relieve skeletal muscle spasms in acute musculoskeletal conditions (64). NSC 78206 is a tricyclic analog compound, which may be relevant because tricyclics and their active metabolites have been shown to have various biological functions, such as modulation of TLR4 and TLR2 signaling (36), whose expression and signaling are known to affect HCV (33,50,76) and inhibition of the drug-metabolizing enzyme aldehyde oxidase (55). In this study, we found that NSC 78206 inhibited JFHpp entry ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also notable is the tricyclic compound NSC 78206 (c3), as tricyclics or their active metabolites are believed to exert their biological actions, in part, via modulation of Toll-like receptor 4 (TLR4) and TLR2 signaling (36). Likewise, HCV infection correlates with TLR expression and signaling (33,50,76). Because this available information collectively highlighted that each of the 18 compounds identified could potentially affect HCV at distinct and multiple steps during infection, we proceeded to determine the steps inhibited by each of the candidate compounds.…”
Section: Screening Of Anti-hcv Compounds Using a Cell-based Hcvcc Infmentioning
confidence: 99%
“…Using a coculture system, Shankar et al (2010) found that the priming of Tcells by DCs pulsed with HIV caused an upregulation of an array of negative costimulatory molecules on T-cells and increased expression of CTLA-4 and FOXP3 when compared to priming with mockpulsed DCs. Wang et al (2010) studied 31 chronic hepatitis C patients and 20 healthy controls, and found significant correlations between TLR2 and Treg numbers. These data suggested that Nef induced TLR2 up-regulation could mediate Tregs expansion.…”
Section: Discussionmentioning
confidence: 96%
“…These Treg were characterized by a fully differentiated and highly activated phenotype, although approximately half of them did not express CD25. Several studies have reported a correlation between viral load and Treg levels during chronic infection, even though this is not always the case [32,[35][36][37].…”
Section: Hcv Infection and Tregmentioning
confidence: 93%